2016
DOI: 10.17140/ooj-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Sub-Tenon Triamcinolone Injection for Chronic Macular Oedema Associated With Non-Ischemic Branch or Central Retinal Vein Occlusion

Abstract: CitationTran HV, Ambresin A, Pournaras J-A, Sabani I, Wolfensberger TJ. Posterior sub-tenon triamcinolone injection for chronic macular oedema associated with non-ischemic branch or central retinal vein occlusion. Methods: Fourteen consecutive eyes of 14 patients characterized by macular oedema lasting more than 3 months and with a visual acuity of less than 20/40 were enrolled. Six eyes presented with BRVO, 8 eyes with CRVO. PST injection of 40 mg TA was performed in topical anaesthesia. All patients were pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The most significant consequence, elevated intraocular pressure, affected 50% (two of four) patients, requiring one or more topical medications for reduction. This is higher than reported in prior studies of sub-tenon's triamcinolone monotherapy for macular edema secondary to retinal vein occlusions [7][8][9]. Due to the small sample size, however, it is unclear if the results would have been different if there was a larger patient sample.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The most significant consequence, elevated intraocular pressure, affected 50% (two of four) patients, requiring one or more topical medications for reduction. This is higher than reported in prior studies of sub-tenon's triamcinolone monotherapy for macular edema secondary to retinal vein occlusions [7][8][9]. Due to the small sample size, however, it is unclear if the results would have been different if there was a larger patient sample.…”
Section: Discussionmentioning
confidence: 58%
“…Steroids reduce vascular permeability and also affect gene expression of inflammatory mediators [6], in addition to their ability to block VEGF. Sub-tenon's triamcinolone monotherapy has been shown to improve visual acuity at one month after administration for retinal vein occlusion, but has varying efficacy in regard to OCT thickness reduction [7][8][9]. These studies have shown rates of IOP elevation from 5%-29% of patients treated with posterior sub-tenon's triamcinolone monotherapy for macular edema secondary to retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Veritti et al [7] used the formulated TA injection in macular edema secondary to diabetes and found improvement in the visual acuity in 90% of the included subjects, which is in line with our study although different injection sites and populations it strengths our idea that addition of both [sodium hyaluronate, and chondroitin sulfate] increase the efficacy of TA in treating of the macular edema. Tran et al [10] looked at 14 eyes for more than three months that had macular edema. They found that PSTA injection is effective in treating macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective interventional non-comparative study by Gurram et al [15] used PSTA to treat 24 eyes of 24 patients with recent-onset non-ischemic, resulting in out of the 24 eyes, 19 [79%] showed an improvement of more than five letters after a month of treatment with increased in the mean BCVA from 30.08 ± 10. 16 Another study conducted by Tran et al [16] examined fourteen eyes from 14 individuals with macular edema for more than three months. They demonstrated that PSTA injection is effective in the treatment of macular edema post-RVO, which agree with our findings, but they report an increase in IOP, which increased from 16.2 mm Hg at the baseline to 18.0 mm Hg after six month, which disagrees with our finding and this may be due to their small sample size and our addition of sodium hyaluronate and chondroitin sulfate.…”
Section: Agreement and Disagreement With Previous Studiesmentioning
confidence: 99%